Mature students using mobile devices in life and learning - Kukulska-Hulme, Agnes (2011)
The paper reports on research concerned with learners’ uses of mobile technologies based on an international survey which targeted students registered on selected master’s and doctoral programmes in Australia, Hong Kong, Portugal, Sweden and the United Kingdom. The survey findings were enriched by local knowledge, as the authors administered questionnaires in their own countries. The research gives an account of uses of handheld devices by students from departments of education, educational technology, engineering, and information technology, in the domains of learning, work, social interaction and entertainment. It illuminates learners’ choices in the midst of evolving social practices, and challenges the common preconception that mobile devices are not suitable for academic study. In today’s global education marketplace, educators need to get to know the technology habits and expectations of their students, including those from other countries. Knowing about students’ previous practices and the techno-cultural setting they come from, can help institutions to determine what types of mobile applications will be most appropriate to support learning.